Pengaruh Penggunaan Slogan Pada Iklan Terhadap Keputusan Pembelian Konsumen Teh Botol Sosro Dengan Mediasi Kesadaran Merek - Yasmin Salsabilla; Aripin Ahmad; Dwi Asri Ambarwati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This research aims to determine "The Effect of Using Slogans in Advertisements on Consumer Purchasing Decisions for Sosro Bottle Tea Mediated by Brand Awareness". In this research there are three variables, namely, slogans in advertisements as the independent variable, purchasing decisions as the dependent variable, and brand awareness as the mediating variable. The research method used in this research is quantitative with a descriptive approach distributed to 100 respondents using a questionnaire distributed online with a Likert scale technique. Based on the problem formulation and discussion of research results, the following conclusions are obtained: (1) Slogans have a significant effect on brand awareness. (2) Slogans have a significant effect on purchasing decisions. (3) Brand awareness has a significant effect on purchasing decisions. (4) Slogans do not have a significant effect on purchasing decisions through brand awareness as a mediating variable.